Assessment of computer modeling accuracy in floodplain hydraulics. (3rd April 2017) - Rao, P.; Hromadka, T. V.; Huxley, C.; Souders, D.; Jordan, N.; Yen, C. C.; Bristow, E.; Biering, C.; Horton, S.; Espinosa, B.
Abstract: In this paper, we examine the performance of several popular hydraulic computer models in predicting the magnitude and location of a hydraulic jump. The computer programs considered include the standard HEC-RAS one-dimensional (1-D) models, as well as computational fluid dynamics models. Other computer programs considered include one-, two-, and three-dimensional (2-D and 3-D) models of both the steady and unsteady flow types. The computational model results are compared with experimental data from two different laboratories. It is shown that a few of these commonly used computer models miss the prediction of the hydraulic jump entirely and produce water surface profiles that are not proper estimates. Although the laboratory tests are one-dimensional steady-state scenarios, the failure of some of the multi-dimensional computer models to predict the likely occurrence of the hydraulic jump, or even provide an indication that the flow conditions are favorable for a jump to occur, indicates that care should be taken both while choosing the model for the application of interest and in interpreting the end results.